Cloud Computing c - Avresky, Dimiter R.; Diaz, Michel; Bode, Arndt; Ciciani, Bruno; Dekel, Eliezer; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book shows the conference proceedings of CloudComp 2009 held in Munich, Germany, in October 2009.
Cloud Computing Infrastructure Track Session 1 -- Executing Distributed Applications on Virtualized Infrastructures Specified with the VXDL Language and Managed by the HIPerNET Framework -- High Performance Parallel Computing with Clouds and Cloud Technologies -- Cloud Computing Platforms Track Session 1 -- Cloud@Home on Top of RESERVOIR -- AppScale: Scalable and Open AppEngine Application Development and Deployment -- Cloud Computing Infrastructure Track Session 2 -- Mitigating Security Threats to Large-Scale Cross Border Virtualization Infrastructures -- Activity Control in Application Landscapes A Further Approach to Improving Maintainability of Distributed Application Landscapes -- PerfCloud: Performance-Oriented Integration of Cloud and GRID -- Combining Cloud and Grid with a User Interface -- Cloud Computing Infrastructure Track Session 3 -- A Performance Analysis of EC2 Cloud Computing Services for Scientific Computing -- Cyberaide Virtual Applicance: On-Demand Deploying Middleware for Cyberinfrastructure -- Cloud Computing Platforms Track Session 2 -- Service Supervision Patterns: Reusable Adaption of Composite Services -- Cloud Computing Platforms Track Session 3 -- Self-managed Microkernels: From Clouds towards Resource Fabrics -- Proactive Software Rejuvenation Based on Machine Learning Techniques -- Dynamic Load Management of Virtual Machines in Cloud Architectures -- Cloud Computing Platforms Track Session 4 -- Dynamic Service Encapsulation -- Modeling Movable Components for Disruption Tolerant Mobile Service Execution -- Cloud Computing Applications Track Session 1 -- Virtual Distro Dispatcher: A Light-Weight Desktop-as-a-Service Solution -- On Cost Modeling for Hosted Enterprise Applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Software Engineering; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval